HUBUNGAN PEMBERIAN MP-ASI DENGAN STATUS GIZI BAYI 6- 24 BULAN - Auliya Shobah (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2021)
Background: Around 17.7% of children in Indonesia suffer from malnutrition. The incidence of malnutrition is related to the food provided by his parents. Objectives: This research was conducted to analyze the relationship between giving weaning food with nutritional status of children aged 6-24 months in Posyandu of Segaraja Village Bekasi Regency. Methods: The study design used was associative observational analytic and was carried out on 62 samples with a purposive sampling method. Data collection using a questionnaire consisting of several characteristics of the respondent namely the age of the child, the sex of the child, the age of the mother, mother's education, mother's occupation, history of exclusive breastfeeding, history of premature birth, socio-economic family, type of weaning food given to the child and child nutrition status. Results: Chi-square analysis test obtained a value of p = 0.229 (> α = 0.05) which means that that there is no relationship between the type of complementary feeding with nutritional status in infants aged 6-24 months in Regional Posyandu of Segarajaya Village Bekasi Regency. Conclusions: Suggestions for further research in order to carry out research with a wider population and use current weight and height data to determine the child's actual nutritional status.